(untitled) (London Journal of Research In Humanities and Social Sciences, 2023)
informative archaeological and historical sources. It contains the complex of articles intentionally hidden into the ground after the appointed process of its collecting. Investigation of such finds is one of the actual problems in the world and home archaeology. On the territory of South Siberia, the buried treasures (or the so-called «caches») appeared as long ago as the Mesolithic Epoch. However, they contained complexes of various kinds of articles and were widespread in the Metals Epoch, especially in the period of the Early Iron Age[Tallgren,1917]. On the vast spaces, from the Middle Yenisey River to the Upper Ob River, quite a number of hidden treasures have been discovered. Among them – the Iyus and Kosogolsk caches, Znamensk, Novoobintsevsk, Burbinsk and a series of the other ones Naschekin, 1967;Martynov, 1973;Stepnayapolosa…, 1992;Vadetskaya, 1999;Borodovskij, Larichev, 2013;Makarov, 2013Borodovskij, Oborin, 2018].